Assessment of Adiponectin and Resistin Indexes Compared to FBG and Useful as Diagnostic Biomarkers in Insulin Resistance and Type 2 Diabetes - Omar, Salah; Higazi, Hassan; Babker, Asaad Mohammed Ahmed; Mohammed, Sara Mohammed Ali; Eltoum, Abd Elgadir (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract: Background and aim: The world prevalence of diabetes among adults will be 6.4%, affecting 285 million adults, in year 2010, and will increase to 7.7% and 439 million adults by year 2030. Insulin resistance is a prerequisite root factor for development of type 2 diabetes (T2DM). Adiponectin and resistin are adipokines which modulate insulin action, energy, glucose and lipid homeostasis. Meta-analyses showed that hypoadiponectinemia and hyperresistinemia are strongly associated with increased risk of insulin resistance, type 2 diabetes (T2DM), Methods: In this case control study, A total 204 Sudanese males and females were recruited to participate in this study (102 diabetic and 102 non-diabetic) and venous blood samples were collected. Serum levels of blood glucose were measured using the particle-enhanced immunoturbidimetric assay method Cobas C-311®.While Adiponectin and Resistine estimated by ELISA Kits. Results: In this results shows significant difference between the means fasting blood glucose (FBG), adiponectin, resistine of diabetic patient and non-diabetic patient. FBG (mean + SD) (164.5 ± 16.7) versus (95.7 ± 13.6), P = 0.041, adiponectin (mean + SD) (5.9 ± 1.6) versus (10.1 ± 1.3), P = 0.037, resistine (mean + SD) (18.2 ± 2.7) versus (12.2 ± 1.1), P = 0.023. In this study, observed from this results strong negative Correlation between the levels of serum Adiponectin and Fasting Blood Glucose, Adiponectin and Resistine. (P.value = 0.013, r = -7.9). (P.value = 0.019, r = -6.6). While showing in the other side moderate positive Correlation between the levels of serum Resistine and Fasting Blood Glucose. (P.value = 0.015, r = 6.0). Conclusion: Iccrease of Resistine and Fasting Blood Glucose and reduced of Adiponectin in diabetic patient compare to non-diabetic patient can be useful as diagnostic biomarkers. Keywords: Adiponectin and Resistin, insulin resistance, type 2 diabetes